If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11u = 22 Solving -11u = 22 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Divide each side by '-11'. u = -2 Simplifying u = -2
| 1-6x+5=12 | | 4.50m+.15c=9 | | x(9x+9)=4x^2-2x+36 | | 222/12 | | 8x-20=15+x | | 3x+5=x+4x+5-2x | | (x-4)=8-16 | | -11=17x | | 1234+5432=6666 | | -34=-x/6 | | 2g+3=a-x | | -4w=16-2w | | x+20=200 | | 11/4X=187/16 | | -5(1x+6)=-75 | | 2x+6x=8x+1 | | 2(3x+5)=6x+9 | | -10(-3+k)=140 | | -6(6+x)=0 | | 22=h/4-5 | | -95+-15y=-605 | | -14n=196 | | y/9=-37 | | 12x-140=940 | | 8b+4=(b-7) | | 5-5d=2d-16 | | -4(9+6x)=36 | | 4p=s+5p | | 12x=1080 | | -0.005+x/100=3x/100+0.07 | | -x+3=x-9 | | x/2+10=27 |